Cross‐sectional study on sensitization to mite and cockroach allergen components in allergy patients in the Central European region. Issue 1 (4th June 2018) - Panzner, Petr; Vachová, Martina; Vlas, Tomáš; Vítovcová, Petra; Brodská, Petra; Malý, Marek
Abstract: Background: The major sources of allergens in the indoor air include house dust mites, dander derived from domestic animals and rodents, cockroach, and several fungi. Mites are the main cause of allergies in some countries with a warmer climate, but the epidemiological significance of mite and cockroach allergens in Central Europe has not been established yet. Methods: We assessed sensitization profiles of allergy patients in a Central European region in regard to sensitization to mites and cockroach. We used molecular diagnosis by means of the microarray ISAC, and we investigated 1766 patients with clinical suspicion to an allergic disorder. 1255 of them were positive to at least one allergen component, and this group was subjected to statistical analysis. Results: The sensitization to at least one mite‐specific molecule (Der p 1, 2, Der f 1, 2) was observed relatively frequently in 32.7% of patients. Specific IgE to mite group 2 molecules is almost fully cross‐reactive. Group 1 allergens are also cross‐reactive, but in some patients, a species‐specific response was observed. Relatively high rate of sensitization both to group 1 and 2 allergens in our patients indicates the greater role of co‐sensitizations. Isolated sensitizations to molecules derived from glyciphagid mites Lep d 2 and/or Blo t 5 without sensitization to other mite‐derived molecules were observed only exceptionally (in 0.6% of cases). True sensitization to at least one cockroach‐specific molecule (Bla g 1, 2, 5) was very rare (in 0.6% of cases), and nearly all of them were co‐sensitizations with other noncockroach‐derived molecules. Sensitization to an inhaled tropomyosin was observed rarely in 2.2% of patients (Der p 10 in 1.9% and Bla g 7 in 1.5%). Co‐sensitization of inhaled tropomyosins with the respective mite‐ or cockroach‐specific molecules was observed only in the minority of patients suggesting the different route of sensitization being more frequent. Conclusions: The majority of patients are co‐sensitized to several molecules of the respective allergen source. The knowledge of this molecular spectrum of sensitization is important for optimal diagnosis and treatment in respect to allergen content in mite extracts used for diagnostic and therapeutic purposes. In regard to the sensitization patterns of Central European patients, it is necessary to point out the importance of quantifying at least three major mite components Der f 1, Der p 1 and Der f 2 (or Der p 2).